2018
DOI: 10.3389/fbioe.2018.00009
|View full text |Cite
|
Sign up to set email alerts
|

Implantation of Neural Probes in the Brain Elicits Oxidative Stress

Abstract: Clinical implantation of intracortical microelectrodes has been hindered, at least in part, by the perpetual inflammatory response occurring after device implantation. The neuroinflammatory response observed after device implantation has been correlated to oxidative stress that occurs due to neurological injury and disease. However, there has yet to be a definitive link of oxidative stress to intracortical microelectrode implantation. Thus, the objective of this study is to give direct evidence of oxidative st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
98
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 78 publications
(107 citation statements)
references
References 88 publications
(129 reference statements)
1
98
0
Order By: Relevance
“…However, electrode insertion induces a rampant foreign body response that activates NADPH oxidase (NOX) (Figure 7B) in multiple cell types acting as phagocytes, especially microglia, to produce reactive oxygen and nitrogen species [108115], which can be referred to as a respiratory burst [116]. In fact, Potter et al [117] and Ereifej et al [118] demonstrated the presence of superoxide anions and the oxidation of nucleic acids, lipids, and proteins, respectively, surrounding electrode sites, confirming local oxidative stress at electrode sites.…”
Section: Discussionmentioning
confidence: 99%
“…However, electrode insertion induces a rampant foreign body response that activates NADPH oxidase (NOX) (Figure 7B) in multiple cell types acting as phagocytes, especially microglia, to produce reactive oxygen and nitrogen species [108115], which can be referred to as a respiratory burst [116]. In fact, Potter et al [117] and Ereifej et al [118] demonstrated the presence of superoxide anions and the oxidation of nucleic acids, lipids, and proteins, respectively, surrounding electrode sites, confirming local oxidative stress at electrode sites.…”
Section: Discussionmentioning
confidence: 99%
“…Surgical procedures were similar to our previously published methods [ 12 , 20 , 40 , 41 ]. Six male Sprague Dawley rats (8–10 weeks old, ~225 gm) were implanted with silicon, single shank, 16 channel intracortical microelectrodes (NeuroNexus A1x16-3mm-100-177-Z16, NeuroNexus, Ann Arbor, MI, USA) in the primary motor cortex (2mm lateral to midline and 2mm anterior to bregma) for eight weeks.…”
Section: Methodsmentioning
confidence: 99%
“…The implantation of the IME severs vasculature, thus breaching the blood–brain barrier and initiating the inflammatory response [ 14 , 15 , 16 ]. Local microglia and infiltrating macrophages become activated, releasing cytokines, neurotoxic factors, and reactive oxygen species (ROS) [ 17 , 18 , 19 , 20 , 21 ]. The release of cytokines, neurotoxic factors, and ROS around implanted electrodes results in a perpetual foreign body response, death of neurons, and corrosion and delamination of the microelectrode surface [ 20 , 22 , 23 , 24 , 25 , 26 , 27 , 28 ].…”
Section: Introductionmentioning
confidence: 99%
“…As covered in Section 2, many of the functional properties and risk factors associated with neuroimplantable devices stem from material selections and form factor. [120] However, the surgical protocols and methods for implantation, i.e., the implantation procedure, have been shown to greatly contribute to clinical safety concerns, [121,122] fidelity of interfacing, [123] and efficacy of treatment. [123] Historically, the implantation of neural probes-including epicortical systems like ECoG, intracortical systems like the Utah array, and deep brain systems like DBS-have required the use of stereotactic craniotomy.…”
Section: Implantation-related Risk Factorsmentioning
confidence: 99%